Odzivanje staršev na želje otrok po izdelkih iz oglasov - Gradišek, Polona (Psihološka obzorja (Ljubljana), 2011)
In our study we investigated how children express their wishes for products advertised on television and how parents respond to their children's wishes. 133 parents of children between 3 and 9 years of age filled in three questionnaires: Questionnaire on children's and parents' response to television advertising, Parental control of children's television viewing (an adapted version) and Family functioning scales. Results have shown that children usually tell their parents about their wishes or ask for a specific product several times. They rarely nag with the intention of getting a product. Parents react differently to their children's wishes: most of them usually explain to their children that they cannot get everything they want or they reconsider whether the child really needs a certain product. They rarely come up with excuses. We have found significant correlations between parents' purchasing styles and their reactions to children's requests. Those parents who tend to buy items which they were not planning to get, comply their children's wishes more often than those who stick to what they intended to purchase in the first place. Findings of the study were used to prepare a list of useful strategies for parents and teachers - how to discuss the effects of advertising with children.
Keywords: advertising; oglaševanje; television; televizija; vloga staršev; parent role; television advertising; televizijsko oglaševanje; vedenje potrošnikov; consumer behavior; children; vedenje; parents; child; otroci; starši; teachers; Questionnaire on children's and parents' response to television advertising; učitelji; Vprašalnik o odzivih otrok in staršev na oglaševanje; Parental control of children's television viewing (an adopted version); Family functionning scales (ICPS); Prilagojen vprašalnik starševskega nadzora otrokovega gledanja televizije; Lestvica funkcioniranja družine (ICPS)